“Glass Ceiling” and Career Progression: The Women Bank Employees in Metro Manila - Barreno, Anna Graziella (Philippine Journal of Labor and Industrial Relations; Vol 35 (2018): Philippine Journal of Labor and Industrial Relations, 2021)
Merging human capital theory and social feminism as groundwork, this research examines the perceptions of women bank employees about the glass ceiling and its effects on career progression. The glass ceiling is viewed by women as an invisible barrier that hinders and or delays their career advancement because of gender discrimination. Data for this study were obtained from two banks in Metro Manila through six focus group discussions (FGD) and 10 key informant interviews (KII) with an inclusion criteria. Women bank employees of at least 25 years of age, either an officer or rank-and-file, and has spent at least five years working for the target banks were considered for the study. The significant findings include: (a) the subjects perceived that the glass ceiling has been cracked with the appointment of women to top and middle management positions; (b) women bank employees experience gender stereotyping brought about by societal roles, which is influenced by Filipino culture and practices; (c) due to societal roles assigned to women, some experience a career plateau, struggles in navigating new assignments and difficulties in getting a promotion; and (d) labor unions and the bank management should work together to provide a more conducive working experience for women employees, specifically their participation in vital decision-making.